1997
DOI: 10.1021/es970163w
|View full text |Cite
|
Sign up to set email alerts
|

222Rn as a Partitioning Tracer To Detect Diesel Fuel Contamination in Aquifers:  Laboratory Study and Field Observations

Abstract: The use of 222 Rn, a naturally occurring radioactive isotope, was investigated as a partitioning tracer to detect and quantify the amount of non-aqueous-phase liquids (NAPLs) in contaminated aquifers. Diesel fuel was chosen as a model NAPL. The diesel fuel-water partition coefficient for 222 Rn was 40 ( 2.3, in bottles containing diesel fuel and water at 12°C. In water-saturated quartz sand contaminated with diesel fuel, the 222 Rn emanating from the sand partitioned between diesel fuel and water as expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 18 publications
3
47
0
2
Order By: Relevance
“…For alcohol tracers, Knw increases with increasing tracer hydrophobicity and decreases with increasing NAPL hydrophobicity (10). The agreement that was generally observed between results obtained with tracer experiments and data from soil core sampling (5,6,8,9) suggests that the retardation of partitioning tracers indeed is determined by Sn and Knw. However, a systematic study has not been conducted to determine whether this relation holds for NAPLs present in various porous matrices and at different surface area-tovolume ratios.…”
Section: Introductionsupporting
confidence: 68%
“…For alcohol tracers, Knw increases with increasing tracer hydrophobicity and decreases with increasing NAPL hydrophobicity (10). The agreement that was generally observed between results obtained with tracer experiments and data from soil core sampling (5,6,8,9) suggests that the retardation of partitioning tracers indeed is determined by Sn and Knw. However, a systematic study has not been conducted to determine whether this relation holds for NAPLs present in various porous matrices and at different surface area-tovolume ratios.…”
Section: Introductionsupporting
confidence: 68%
“…The same concept but a different tracer philosophy is the background of the PTT experiments performed by Hunkeler et al (1997) and Semprini et al (2000). While all aforementioned studies used artificial tracers these authors used a naturally occurring radioactive isotope, 222 Rn, that is found in groundwater as a dissolved gas, as partitioning tracer to detect and quantify residual NAPLs in contaminated aquifers.…”
Section: Application Of Multitracer Forced Gradient Transport Experimmentioning
confidence: 99%
“…Schubert et al ( , 2007a carried out laboratory experiments to determine the partition coefficients /< N APL/W and /< N APL/AIR for commercial mixtures of petroleum hydrocarbons (gasoline, diesel, kerosene) and demonstrated the ability of NAPL accumulations to act as geochemical traps for Rn. The resulting reduction in Rn activity in the soil air of the vadose zone should therefore indicate the presence of underlying levels with high hydrocarbon saturation (Hunkeler et al, 1997;Semprini et al, 2000;Schubert et al, 2001Schubert et al, , 2005Schubert et al, , 2007b. Field tests and laboratory experiments published by Schubert et al (2007c), Fan et al (2007), Davis et al, (2002Davis et al, ( , 2003 and Semprini et al (2000) suggest that Rn can be used as a non-conservative tracer to estimate LNAPL saturation in the subsurface.…”
Section: Jj Physico-chemical Backgroundmentioning
confidence: 99%